Delayed winter supplemental feeding and year-round mineral supplementation of beef cows on native range - J. Pruitt; R.R. Schalles; L.H. Harbers; Clenton E. Owensby; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1979)
Polled Hereford cows on native Flint Hills pasture not supplemented until February lost more weight from December to February, lost less from February to May, and were in poorer condition before calving than cows supplemented beginning in November. But calf survival, birth weight, and calf average daily gain were similar for both groups. Feeding cows a calcium, phosphorus, trace mineral mix did not improve any measure of cow or calf performance.
Keywords: Cattlemen& #x27; s Day; 1979; Report of progress (Kansas State University. Agricultural Experiment Station); 350; Beef; Mineral supplementation; Native range; Supplemental feeding